Combating Transnational Crimes Trafficking in Women from a Feminist Perspective Legal Theory - Indra Firmansyah; Muh. Endriyo Susila; Fandi Ahmad Fahreza (CV. Strata Persada Academia, 2023)
The data shows that the transnational crime of trafficking in women is increasing every year. Starting from prostitution, migrant workers to narcotics smuggling carried out by women who are victims of trafficking in women. Various legal efforts have been made by both international institutions and the Indonesian government. One of the obstacles faced is the feminization of poverty where women experience economic difficulties that make them tempted and trapped either intentionally or not, in the vortex of women's trafficking syndicates. In addition, the alignment of the state, which is still strong patriarchal, is still felt to be not in favor of women. This research focuses on the defense of Feminist Legal Theory against women where the law, especially in Indonesia, it has not fully sided with the welfare of women, which makes women avoid the crime of trafficking in women. This normative juridical research shows that the problem of trafficking in women is not only a legal issue, but more than that it is a welfare issue that must be obtained by all citizens, especially women so as to prevent them from transnational crimes of trafficking in women.